Solid oxide fuel cells : from fundamental principles to complete systems - Maric, Radenka; Mirshekari, Gholamreza (Boca Raton : CRC Press, 2020)
"This book is as a valuable resource for beginners as well as for experienced researchers and developers of solid oxide fuel cells. It provides a fundamental understanding of SOFCs by covering the present state-of-the-art as well as ongoing research and future challenges to be solved. It discusses current and future materials and provides an overview of development activities with a more general system approach toward fuel cell plant technology, including plant design and economics, industrial data and advances in technology"--
Fundamental Aspect of Solid Oxide Fuel Cells. Materials: Electrolytes, Anodes, Cathodes, Interconnects and Sealants. Processing. Cell and Stack Configuration. System Design and Optimization. Fuel Cell System Economics. Research and Demonstration Activities in United States, Asia and Europe.
OCLC-licensed vendor bibliographic record.
Keywords: Solid oxide fuel cells; SCIENCE / Chemistry / Industrial & Technical; SCIENCE / Energy; TECHNOLOGY / Engineering / Chemical & Biochemical